Shakespeare's Blush, or "the Animal" in Othello. (2nd January 2016) - Swarbrick, Steven
Abstract : This essay examines how the rhetoric of animalization in Shakespeare's Othello compels us to think early modern categories of race in connection with early modern discourses of "human" versus "animal." Beginning with Shakespeare's representation of Iago, I suggest that it is the potential for sameness conditioned by Iago's counterfactual statement ("Were I the Moor, I would not be Iago") that is most significant about his relation to Othello. From there I consider the overlap between the play's representations of animality and black skin. Read in the context of Jacques Derrida's reflections on animals, I consider the deconstructive value of linking the play's animalizing language to the affect of shame. With its focus on the blush, Shakespeare's Othello shows that the affect of shame cannot be countered with a simple return to the "human, " since it is precisely the category of the human that the play's animal and racial bodies deconstruct. Read so, this essay examines not only the negative side of animalization, which mediates categories of "the other, " but also the positive potential of cross-species relations for interrogating race in Shakespeare's play.